The effect of service quality and shariah compliance on customer loyalty by mediating customer satisfaction - Buyung Romadhoni; Asbi Amin; Arnida Arnida (Annals of Management and Organization Research, 2025)
Purpose: This research to examine the influence of Service Quality and Shariah Compliance on Customer Loyalty; Service Quality and Shariah Compliance influence customer satisfaction; Customer Loyalty influences Customer Satisfaction; Service Quality and Shariah Compliance towards Customer Loyalty by mediating customer satisfaction. Methodology/approach: This study uses a quantitative descriptive research. Taken from clients of PT Bank Syariah Indonesia KCP Makassar Panakukang with a test estimate of 150 respondents. Results: Service quality, Shariah Compliance and customer satisfaction has a positive effect on customer loyalty; service quality and Shariah Compliance has a positive effect on customer satisfaction; service quality has a positive effect but Shariah Compliance has not effect on customer loyalty through customer satisfaction. Conclusion: Of the seven hypotheses found, six were accepted but one hypothesis was rejected. Limitations: A survey of 150 clients at one branch, which restricts the generalizability of the findings to all customers of PT Bank Syariah Indonesia in Makassar. Contribution: It is hoped that the results of this research can provide information on marketing strategies in sharia practice, especially in improving service quality, sharia compliance, customer satisfaction in increasing customer loyalty.